Consortium of Journals - Gayatri, D.; Sridhar Kumar, M. (Journal of Information and Knowledge, 2014)
For quite some time, libraries have been suffering under the "information crisis" facing not only the constant increase in the number of journal titles but also due to a routine increase in the price of journals, hike in currency conversion rate, initiation in infrastructural set up and work force. Collective move always gives fruitful results. Library constortium is a collective activity of a group of libraries to cope up with the above mentioned crisis. This paper covers the concept of the library consortium with its various activities and responsibilities.